Rooftop Solar Development in Bali’s Energy Transition: Policy Implementation and Governance Challenges - Anak Agung Gede Oka Wisnumurti; Anak Agung Ayu Dewi Larantika; Carolina Augi Widya Putri (Politicos: Jurnal Politik Dan Pemerintahan, 2026)
Bali, as a major tourist destination, has experienced a significant increase in energy consumption due to the growth of the tourism industry, leading to increased energy demand. Consequently, Bali needs to achieve energy self-sufficiency, as energy self-sufficiency not only contributes to environmental sustainability but is also a pillar of sustainable development. Bali Governor Regulation No. 45 of 2019 on Bali Energi Bersih (BEB) is a policy aimed at strengthening Bali’s energy supply through the promotion of renewable energy development, including rooftop solar power plants. However, the expansion of rooftop solar systems in Bali remains limited. Previous studies have mainly focused on technical and economic aspects, while limited attention has been given to the gap between policy ambition and implementation outcomes. This study aims to analyze the development of rooftop solar power plants before and after the Bali Clean Energy policy, and to identify the driving and inhibiting factors affecting their role in achieving energy self-sufficient in Bali Province. This study employs a qualitative descriptive research method. The data collection methods used include observation, interviews, and documentation. The findings show that the policy has increased awareness and encouraged initial rooftop solar adoption. However, implementation has not yet been optimal. The main barriers include high upfront investment costs, limited financing access, shortages of competent installation personnel, and regulatory uncertainty caused by changes in central government policies. These challenges have reduced public confidence and slowed adoption rates. This study fills the gap in local level policy implementation of energy transition by showing that renewable energy transition depends not only on technological readiness, but also on regulatory consistency, institutional capacity, and effective coordination between provincial and central governments.